2014
DOI: 10.1542/peds.2014-0690
|View full text |Cite
|
Sign up to set email alerts
|

Etiologies for Seizures Around the Time of Vaccination

Abstract: OBJECTIVES: This study was an assessment of the incidence, course, and etiology of epilepsy with vaccination-related seizure onset in a population-based cohort of children. METHODS: The medical data of 990 children with seizures after vaccination in the first 2 years of life, reported to the National Institute for Public Health and Environment in the Netherlands in 1997 through 2006, were reviewed. Follow-up data were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 34 publications
0
25
0
3
Order By: Relevance
“…Bu çalışmada, aşı sonrası konvülziyon geçiren 6 hastada epilepsi tanı grubunda yer alıyordu. Bu hastalarda aşı dışında başka bir uyaranda, ateş ya da enfeksiyon gibi, kronik nörolojik disfonksiyonu tetikleyebilir (17)(18)(19)(20). Ayrıca aşı sonrası konvülziyon geçiren çocukların değerlendirildiği başka bir çalış-mada çoğu çocuğun altta yatan nörolojik ya da nörogelişimsel kolaylaştırıcı bir yatkınlığı olduğu gösterilmiştir (18).…”
Section: Tanı Grubu Aşılamaya Ara Verilenler N (%)unclassified
See 1 more Smart Citation
“…Bu çalışmada, aşı sonrası konvülziyon geçiren 6 hastada epilepsi tanı grubunda yer alıyordu. Bu hastalarda aşı dışında başka bir uyaranda, ateş ya da enfeksiyon gibi, kronik nörolojik disfonksiyonu tetikleyebilir (17)(18)(19)(20). Ayrıca aşı sonrası konvülziyon geçiren çocukların değerlendirildiği başka bir çalış-mada çoğu çocuğun altta yatan nörolojik ya da nörogelişimsel kolaylaştırıcı bir yatkınlığı olduğu gösterilmiştir (18).…”
Section: Tanı Grubu Aşılamaya Ara Verilenler N (%)unclassified
“…Bu hastalarda aşı dışında başka bir uyaranda, ateş ya da enfeksiyon gibi, kronik nörolojik disfonksiyonu tetikleyebilir (17)(18)(19)(20). Ayrıca aşı sonrası konvülziyon geçiren çocukların değerlendirildiği başka bir çalış-mada çoğu çocuğun altta yatan nörolojik ya da nörogelişimsel kolaylaştırıcı bir yatkınlığı olduğu gösterilmiştir (18). Bu nedenle nörolojik problemleri olan hastalarda bireysel değerlendirme yapılarak aşılamanın yararları ve hastanın riskleri düşünülerek dikkatli bir planlanma yapılmalıdır.…”
Section: Tanı Grubu Aşılamaya Ara Verilenler N (%)unclassified
“…These observations provide further evidence for an underlying genetic cause for which the vaccine triggers the initial seizure. Further, they emphasize that the outcome of vaccine-related seizures may be excellent in patients without encephalopathy (7).…”
Section: Vaccination Triggers Rather Than Causes Seizuresmentioning
confidence: 99%
“…The etiologies and pathophysiology may vary depending on the patient and the risk factors (head trauma, central nervous system infections, febrile seizures, developmental history, and medications/toxin exposures) [7]. Recent studies reported that genetic or structural defects are the underlying causes of seizures, which may be activated after vaccination presumably due to the interplay of the innate biology of the body [8].…”
Section: Introductionmentioning
confidence: 99%